Sº and jarosite behavior during recovery of values from the direct leaching residue of sphalerite using cyanide and glycine - Picazo-Rodríguez N.G.; Carrillo-Pedroza F.R.; Martínez Luévanos A.; Soria-Aguilar M.J.; Almaguer-Guzmán I. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This paper reports the effect of the components of a direct leaching residue (jarosite and elemental sulfur), on the recovery of valuable metals such as gold and silver. Leaching media such as cyanide and mixtures of cyanide with glycine were used to recover the gold and silver from the residue; however, a low recovery of these metals was obtained. This occurred due to the negative effect of its components which caused problems in the extraction process such as encapsulation of silver (due to jarosite) and the formation of thiocyanate and re-precipitation of silver (due to sulfur). Various treatments prior to leaching were tested, finding that when the residue was desulfurized with perchlorethylene and subjected to an oxidizing alkaline hydrothermal treatment, the gold extraction increased from 39.73 to 88% and the silver extraction of 64.76 to 94.29%. Additionally, it was determined that when cyanide was assisted by glycine, the latter decreased the cyanide consumption by inhibition of the dissolution of iron and sulfur in cyanide.